2006
DOI: 10.1007/s10310-006-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of aboveground litter in aCryptomeria japonicaplantation

Abstract: We assessed the vertical distribution of litter and its seasonal patterns in the canopy and on the forest fl oor (soil), as well as litterfall (the fl ux of litter from the canopy to the soil) in a 33-year-old plantation of Japanese cedar (Cryptomeria japonica D. Don). The masses of total litter, dead leaves, and dead branches in the canopy of C. japonica trees averaged 34.09, 19.53, and 14.56 t dry wt ha −1 , respectively, and were almost constant during the study period. The total masses of the annual litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Yoshida & Hijii (2006a) suggested that the densities of X. brevispina per unit weight of litter were similar between canopy litter and forest-fl oor litter. They also reported that the standing arboreal litter in a 33-year-old Cryptomeria forest was several times larger than that of the soil (Yoshida & Hijii, 2006b). This suggests that a considerable part of the population of X. brevispina may be maintained by the arboreal litter in Cryptomeria forests.…”
Section: Resultsmentioning
confidence: 96%
“…Yoshida & Hijii (2006a) suggested that the densities of X. brevispina per unit weight of litter were similar between canopy litter and forest-fl oor litter. They also reported that the standing arboreal litter in a 33-year-old Cryptomeria forest was several times larger than that of the soil (Yoshida & Hijii, 2006b). This suggests that a considerable part of the population of X. brevispina may be maintained by the arboreal litter in Cryptomeria forests.…”
Section: Resultsmentioning
confidence: 96%
“…First, community structures of microarthropods are relatively constant over time with environmental (resource) stability, as suggested by a study of collembolans in the soil of a pine forest (Takeda 1987(Takeda , 1995. Canopy litter of C. japonica trees remains attached to the trunk for several years without remarkable decomposition (Katsuno et al 1984;Miyaura 1989;Kaneko et al 1997), and this material could thus provide stable resources for microarthropods in the canopies (Yoshida and Hijii 2006). Second, annual variations in the densities of microarthropods in dead leaves were relatively small for 2 years in this study, as well as the result from the C. japonica canopy in the same study area by insecticide knockdown (Hijii 1989).…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study of mature Cryptomeria japonica D. Don plantations, there was constantly a large amount of dead branches with foliage that remained attached to the trunk in the lower parts of the canopy; these dead branches and leaves formed a layer of canopy litter (Yoshida and Hijii 2006). To evaluate the numerical and functional traits of microarthropods in such substrates in the canopy, two extraction methods are applied to them: washing and dry extractors.…”
Section: Introductionmentioning
confidence: 99%
“…The canopy of C. japonica, an endemic Japanese evergreen coniferous species, retains a large amount of dead needle-leaves and branches that stay attached to the trunk for several years (Katsuno et al 1984;Yoshida and Hijii 2006b). As a result, a C. japonica forest can establish a litter-abundant ecosystem that enables many detritivorous and fungivorous microarthropods to inhabit the canopy (Hijii 1986(Hijii , 1989Ichisawa et al 1999;Hijii 2005a, b, 2006a).…”
Section: Study Sitesmentioning
confidence: 93%
“…in suspended soils) are abundant (Paoletti et al 1991;Karasawa and Hijii 2008), attaining as much as half of the invertebrate biomass in the canopy (Ellwood and Foster 2004). In temperate forests, coniferous canopies also hold many microhabitats, for example moss mats in a spruce forest (Winchester et al 1999) and dead attached foliage in a Japanese cedar forest (Yoshida and Hijii 2006b). Thus, soil or litter fauna in the canopy have recently been highlighted as important components of the diversity of canopy organisms and of the structure of the food web and its functioning (e.g.…”
Section: Introductionmentioning
confidence: 97%